Penerapan Strategi Packaging Dan Sales Promotion Pada Usaha Dezato Brownie - Dwina arum muninggar; Harifuddin Thahir (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to examine the application of modern packaging and sales promotion strategies in the dezato brownie business. The method used is a case study with a qualitative approach. data was collected through observation, interviews and analysis of related documents. The research results show that the implementation of packaging and sales promotion strategies has had a positive impact on the development of the dezato brownie business. The use of attractive and functional packaging has succeeded in increasing the attractiveness of the product and expanding the market. Apart from that, creative and effective sales promotions can increase consumer awareness and speed up the purchasing process. The practical implication of this research is the importance of adopting modern strategies in packaging products and implementing innovative sales promotions to increase the competitiveness and growth of culinary businesses.